Electro-catalytic oxidation of hemicelluloses at the Au electrode1. Issue 17 (7th May 2015) - Sugano, Yasuhito; Saloranta, Tiina; Bobacka, Johan; Ivaska, Ari
<x xml:space="preserve">Abstract</x> The recently reported electro-catalytic reaction mechanism for the oxidation of cellulose is proposed to work also for the electro-oxidation of other polysaccharides (e.g. hemicelluloses).